2006
DOI: 10.1128/jvi.80.7.3341-3348.2006
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase B/Akt Is Present in Activated Form throughout the Entire Replicative Cycle of ΔUS3 Mutant Virus but Only at Early Times after Infection with Wild-Type Herpes Simplex Virus 1

Abstract: The product of the herpes simplex virus 1 (HSV-1) US3 gene is a multifunctional serine-threonine protein kinase that can block apoptosis induced by proapoptotic cellular proteins, exogenous agents, or replicationdefective viruses. Earlier studies showed that the U S 3 kinase activates and functionally overlaps cellular protein kinase A (PKA). In this study we examined the status of phosphatidylinositol 3-kinase [PI (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 49 publications
7
53
1
Order By: Relevance
“…Previous reports have shown that R7041-infected cells showed enhanced Akt phosphorylation/activation compared with R7306 wild-type-infected cells (31). Our results showed that whereas R7306 infection minimally (in U87 cells) or moderately (in A549 cells) induced Akt phosphorylation, R7041 infection strongly induced Akt activation (Fig.…”
Section: Resultssupporting
confidence: 48%
“…Previous reports have shown that R7041-infected cells showed enhanced Akt phosphorylation/activation compared with R7306 wild-type-infected cells (31). Our results showed that whereas R7306 infection minimally (in U87 cells) or moderately (in A549 cells) induced Akt phosphorylation, R7041 infection strongly induced Akt activation (Fig.…”
Section: Resultssupporting
confidence: 48%
“…In contrast, HSV-1 Us3 suppresses both ERK and PI3K-Akt activity (33,35,36). Furthermore, specific downstream substrates such as GSK3β are regulated independent of host PI3K-Akt signaling and are, instead, directly controlled by Us3 (21,33,37,38). Here, we find that Us3 induces MT acetylation in transfected cells and is required for efficient stable MT formation in infected cells.…”
Section: Discussionmentioning
confidence: 62%
“…Kaposi's sarcoma-associated herpesvirus activates ERK and PI3K through engagement of viral glycoprotein gB with host integrin receptors to stabilize MTs within minutes of infection (9). In contrast, HSV-1 Us3 suppresses both ERK and PI3K-Akt activity (33,35,36). Furthermore, specific downstream substrates such as GSK3β are regulated independent of host PI3K-Akt signaling and are, instead, directly controlled by Us3 (21,33,37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support the matching of MDD groups S2 and T2 with CK2 group. With regard to PKB which is matched with cluster S4, it is reported to be involved in the regulation of the Herpes Simplex virus -1 [25]. Additionally, experimental research also claims that PKB signaling benefits coxsackie virus B3 replication [26].…”
Section: Motifs Comparisonmentioning
confidence: 99%